Jurnal Perencanaan dan Pengendalian Persediaan Bahan Baku Batako di CV Karya Jaya Palembang: Persediaan Bahan Baku Batako - Akbar, Ahsanul; Renilaili, ReniLaili (Jurnal Tekno, 2023)
CV Karya Jaya Palembang is a Pavling Block Factory which operates in the building sector as well as a distributor selling products such as Bricks, Roof Tiles, Concrete, Pillars, Chess, etc. distributors who sell products such as bricks, tiles, concrete, poles, dams, etc. Material vendors are currently experiencing inventory problems. Insufficient stock and does not meet buyers' desires. Therefore, material inventory planning is needed to determine optimal inventory levels. Forecasting calculation methods, EOQ, safety stock, reorder point, and total inventory cost (TIC) are used in this research. The amount of raw material purchases calculated using the EOQ method is 4567% of the optimal amount of raw material purchases. The company has not yet determined the amount of safety stock, but based on the EOQ method, the amount of safety stock that the company will hand over is 309.56 kg. And when the raw material inventory reaches 41,746.19kg, you need to order again.